2016
DOI: 10.3892/or.2016.5023
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β1 regulating miR-205/miR-195 expression affects the TGF-β signal pathway by respectively targeting SMAD2/SMAD7

Abstract: Transforming growth factor-β (TGF-β) proteins are important cytokines in the occurrence and development of tumors. However, its neural functions in glioma are still not understood. In the present study, we evaluated the effects of TGF-β1 on glioma cell line U87. miR-205 and miR-195 were involved in TGF-β1 signaling pathway. Quantitative real-time PCR was used to detect miR-205 and miR-195 levels in human glioma tissue samples and U87 cells treated with different concentrations of TGF-β1. Enzyme-linked immunoso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 40 publications
2
22
0
1
Order By: Relevance
“…To identify the molecular mechanism of miR‐195 and miR‐497 in cancer, we selected the SMURF2 gene among the components of TGF‐β signaling as putative targets of miR‐195 and miR‐497 using prediction databases. In fact, many studies have reported that TGF‐β signaling promotes miR‐195 and miR‐497 expression (Chen et al , ; Duan and Chen, ; Song et al , ), and miR‐195/497 targets other proteins associated with TGF‐β signaling. We analyzed the expression of the SMURF2 gene in tumor and paired normal lung tissues from primary NSCLC patients in the NCBI GEO database (http://www.ncbi.nlm.nih.gov/geo/query/acc.cgi?acc=GSE21933) and lung cancer cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…To identify the molecular mechanism of miR‐195 and miR‐497 in cancer, we selected the SMURF2 gene among the components of TGF‐β signaling as putative targets of miR‐195 and miR‐497 using prediction databases. In fact, many studies have reported that TGF‐β signaling promotes miR‐195 and miR‐497 expression (Chen et al , ; Duan and Chen, ; Song et al , ), and miR‐195/497 targets other proteins associated with TGF‐β signaling. We analyzed the expression of the SMURF2 gene in tumor and paired normal lung tissues from primary NSCLC patients in the NCBI GEO database (http://www.ncbi.nlm.nih.gov/geo/query/acc.cgi?acc=GSE21933) and lung cancer cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to HSCs, Sekiya found that, during primary HSCs (pHSCs) activation, miR-195 was downregulated on the 10th day compared with the 1st day, and miR-195 could decrease cyclin E expression and inhibit cell proliferation induced by interferon-B [ 21 ]. Duan and Chen demonstrated that miR-195 was upregulated by TGF- β 1 in a dose-dependent manner enhancing glioma cell invasion and proliferation in U87 cells [ 22 ]. Growing evidence has demonstrated that miR-195 plays an important role in the neoplastic disease; however, studies on the relationship between miR-195 and liver fibrosis are far from enough.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the results in this study showed that p-AKT was a downstream factor of PTEN. In addition to PTEN/p-AKT signaling pathway, TGF-β signaling pathway also regulates miRNA-205 expression [19], suggesting a possible interaction between different cell signaling pathways.…”
Section: Discussionmentioning
confidence: 99%